Novel co-occurrence of hypophosphatemic rickets with 46XY DSD (disorder of sex development) due to a CYP17A1 variant - A Mondkar, Shruti; Yewale, Sushil; Khadilkar, Vaman; Khadilkar, Anuradha (Indian Journal of Child Health, 2023)
17-α-hydroxylase deficiency causes a rare type of congenital adrenal hyperplasia (CAH). X-linked hypophosphatemic rickets (XLH) is a rare disorder caused by inactivating mutations in the PHEX gene. We report a novel co-occurrence of XLH with 46XY disorder of sex development due to 17-α-hydroxylase deficiency. A young child reared as a girl, presented as a toddler with genu varus, low phosphorus, normal calcium, and parathormone, and was treated as hypophosphatemic rickets. In early childhood, due to short stature and hypertension, the child was investigated for Turner syndrome. Ultrasound revealed intra-abdominal gonads and an absent uterus. The karyotype was 46XY. Investigations revealed low serum cortisol, renin, normal 17-hydroxyprogesterone, and aldosterone. A year later, a bilateral orchidectomy was performed. Two years later, she was referred to us for further management. Adrenocorticotrophic hormone (ACTH), cortisol, renin, deoxycorticosterone, and clinical exome were advised. She was lost to follow-up for 3 years. On follow-up in early adolescence, she was pre-pubertal; biochemical findings of hypophosphatemic rickets, elevated ACTH, low cortisol, and low normal aldosterone were noted. Clinical exome revealed variants in the CYP17A1 gene (homozygous) causing CAH (17-α-hydroxylase) and PHEX (hemizygous) gene causing XLH. Treatment with hydrocortisone, phosphate, cholecalciferol, and calcitriol was commenced. Hypertension is now well-controlled, but genu varus persists and may require surgical correction.